Quality variation and biosynthesis of anti-inflammatory compounds for Capparis spinosa based on the metabolome and transcriptome analysis - Liu, Xiaoying; Aimaier, Alimu; Wang, Weilan; Dong, Yuliang; Han, Peng; He, Jiang; Mu, Lihong; Wang, Xinhui; Li, Jinyao (Frontiers in Plant Science, 2023)
Introduction Capparis spinosa L. fruits as edible and medicinal plant, has anti-inflammatory activities. The different morphological characteristics of C. spinosa fruits from Ili, Turpan, and Karamay may affect their anti-inflammatory components and functions. Methods The anti-inflammatory activity of C. spinosa fruit was assessed using an LPS-induced inflammatory cell model. Furthermore, the differences in anti-inflammatory compounds were analyzed by metabolome and RNA-seq. Additionally, the anti-inflammatory mechanism was elucidated using network pharmacology. Results In the study, we found that the 95% ethanol extracts (CSE) obtained from the three kinds of fruits showed remarkable anti-inflammatory effects both in vivo and in vitro. However, the CSE derived from Ili fruits significantly reduced CD86 levels on DCs. As a result of metabolomic analysis, the metabolic profiles of Ili fruits differed significantly from those of the other two habitats, which were consistent with transcriptome analysis. A total of 15 compounds exhibiting anti-inflammatory activity were subjected to screening, revealing a greater accumulation of flavonoids in the Turpan and Karamay districts. Notably, phenolic compounds were identified as the principal anti-inflammatory components in C. spinosa. Conclusion There were significant differences in the morphology, metabolites, transcriptional levels, and anti-inflammatory activity of C. spinosa from the three districts.